Phosphatidylinositol-4,5-bisphosphate is required for KCNQ1/KCNE1 channel function but not anterograde trafficking - Royal, Alice A.; Tinker, Andrew; Harmer, Stephen C. (PLOS ONE, 2017)
The slow delayed-rectifier potassium current (IKs) is crucial for human cardiac action potential repolarization. The formation of IKs requires co-assembly of the KCNQ1 α-subunit and KCNE1 β-subunit, and mutations in either of these subunits can lead to hereditary long QT syndrome types 1 and 5, respectively. It is widely recognised that the KCNQ1/KCNE1 (Q1/E1) channel requires phosphatidylinositol-4,5-bisphosphate (PIP2) binding for function. We previously identified a cluster of basic residues in the proximal C-terminus of KCNQ1 that form a PIP2/phosphoinositide binding site. Upon charge neutralisation of these residues we found that the channel became more retained in the endoplasmic reticulum, which raised the possibility that channel–phosphoinositide interactions could play a role in channel trafficking. To explore this further we used a chemically induced dimerization (CID) system to selectively deplete PIP2 and/or phosphatidylinositol-4-phosphate (PI(4)P) at the plasma membrane (PM) or Golgi, and we subsequently monitored the effects on both channel trafficking and function. The depletion of PIP2 and/or PI(4)P at either the PM or Golgi did not alter channel cell-surface expression levels. However, channel function was extremely sensitive to the depletion of PIP2 at the PM, which is in contrast to the response of other cardiac potassium channels tested (Kir2.1 and Kv11.1). Surprisingly, when using the CID system IKs was dramatically reduced even before dimerization was induced, highlighting limitations regarding the utility of this system when studying processes highly sensitive to PIP2 depletion. In conclusion, we identify that the Q1/E1 channel does not require PIP2 or PI(4)P for anterograde trafficking, but is heavily reliant on PIP2 for channel function once at the PM.